Correlated mass spectrometry and confocal microscopy imaging verifies the dual-targeting action of an organoruthenium anticancer complex. Issue 29 (29th March 2017) - Liu, Suyan; Zheng, Wei; Wu, Kui; Lin, Yu; Jia, Feifei; Zhang, Yang; Wang, Zhaoying; Luo, Qun; Zhao, Yao; Wang, Fuyi
Abstract : A correlated ToF-SIMS and CLSM imaging strategy was developed to visualize the subcellular distribution of an organoruthenium anticancer complex, showing its accumulation in both cell membrane and nuclei and verifying its dual-targeting feature. Abstract : An addressable single cell imaging strategy combining ToF-SIMS and confocal fluorescence microscopy imaging has been developed, and sucessfully applied to visualize the subcellular distribution of an organoruthenium anticancer complex, [(η 6 -benzene)Ru( N, N -L)Cl] + (1 ; L: 4-anilinoquinazoline ligand), showing its accumulation in both cell membrane and nuclei, and verifying its dual-targeting feature.